Experiences of midwifery students and graduates in Somalia: evidence from qualitative data - Hawa Abdullahi; Asia Mohamed Mohamud; Maryan Abdulkadir Ahmed; Mohamed Ahmed Omar; Abdirisak A. Dalmar; Hannah Tappis; Shatha Elnakib (Frontiers in Global Women's Health)
IntroductionMidwives play an important role in maternal and newborn care, yet are in short supply globally. The shortage in midwives is particularly acute in sub-Saharan African countries, many of which are conflict-affected. Midwives face many challenges that impact their workforce participation and retention, and these challenges are often compounded in conflict settings. Somalia ranks among the countries with the highest maternal mortality rate, with an estimated shortage of 20,000 midwives compared to the WHO recommended standard. Yet, limited research has explored the lived experience of midwives in conflict. This qualitative study seeks to explore the experiences, plans, and aspirations of midwifery students and recent graduates from nine midwifery schools in Somalia and to understand how the safety and security situation impacts their educational experience and willingness to join the profession.MethodsThis is a sub-study embedded within a broader prospective multi-cohort study of midwifery students and early career midwives conducted in 2023 and which will continue until 2025. We invited graduates and students in their final year from eight schools in Mogadishu and one school in Galgadud to participate in the study. This study draws on findings from five focus group discussions conducted with midwifery students and graduates who were included in the parent cohort study, for a total sample size of 33 students and graduates. We conducted thematic analysis using a combination of inductive and deductive coding.ResultsOur data illustrates powerful motivation among midwifery students and graduates to join the profession. Motivation was mostly intrinsic, with participants describing their desire to help the mother-baby dyad and to reduce maternal mortality in their communities as the predominant driving force for joining the profession. Yet, participants cited several barriers to entering the workforce, including harmful gender norms that prioritize women's domestic roles over professional aspirations and societal mistrust toward young midwives. Participants stated that their age and gender undermined them professionally and noted the community's preference for older midwives and traditional birth attendants. Safety and security significantly impacted participants' acceptance of job placement in remote areas and students' ability to attend school regularly. In terms of perceived preparedness, graduates felt well prepared for their role but identified gaps in abortion care, neonatal resuscitation, and usage of basic ultrasound.ConclusionThe challenges faced by midwifery students and newly graduated midwives have direct implications for the health outcomes of mothers and infants in conflict-affected settings. The recurring themes of inadequate training, security risks, and restrictive gender norms require holistic and systematic interventions that address these issues in order to improve motivation and workforce participation among this important health cadre.